Development of Socialist Economic Thought, The : Selected Essays by Maurice Dobb - Dobb, Maurice, 1900-1976 (Book collections on Project MUSE., 2014)
Maurice Dobb (1900-1976) was a highly influential Marxist political economist and economic historian. He was famous for his writings on economic development - including the development of capitalism in the west, and the dilemmas of the Soviet Union in their efforts to industrialise what had been primarily an agricultural country. This collection brings together a selection of essays written in the 1960s and 1970s, on socialist economic thought and planning. The essays discuss many issues of relevance today - how to bring about growth in non-industrialised countries; non-market approaches to the economy; and the relevance of Marx to analysing commodity capitalism. The essays are introduced by Dobb's Literary Executor Brian Pollitt, who also gives a useful introduction to Dobb's life and work. Maurice Dobb was author of many works, including Studies in the Development of Capitalism (1946), Soviet Economic Development since 1917 (revised 1966) and Theories of Value and Distribution since Adam Smith (1973). He also collaborated with Piero Sraffa for many years in his work on Ricardo. Brian Pollitt has worked in Cuba, Chile and Nicaragua. His later research has focused on the problems of transition in socialist economies. He has held teaching and research positions at the Universities of Yale, Massachusetts, Concepcion and Adelaide, and has recently retired from his post at the University of Glasgow.